Implications of Covid-19 on HR practices- workforce strategies in the new normal - Butt, Fatima S (2021)
Covid-19 has disrupted the global economy and triggered changes in the world of work ranging from supply chain operations to people strategies. As the pandemic accelerated, organizations altered their strategies overnight to ensure business continuity to protect their financial health and the well-being of their workforce. The objective of this study is to examine the impact of Covid-19 on HR practices in the areas of compensation, talent management, learning and development and strategic workforce planning. In the aftermath of the pandemic and as organizations move towards the new normal, opportunities can be leveraged on to emerge stronger as an HR function. Keeping this in view the long term impact on each of these variables will also be discussed along with recommendations to build resilient practices designed to drive HR effectiveness. This study undertakes a qualitative approach where seasoned HR leaders from diverse industries were interviewed regarding their experiences and the practices they adopted during Covid-19, the long term impact and recommendations to be incorporated with the objective of gaining a people advantage in the future. The findings demonstrate that in the short run there has been a significant impact on HR practices in the areas of compensation, talent management, learning and development and strategic workforce planning. Similarly, areas of opportunity emerged and recommendations were proposed that organizations can leverage on in order to enhance HR effectiveness in the long run. The recommendation is for leaders to be heedful of theoretical models such as Maslow’s hierarchy and the resource based view while developing their practices as it has implications on HR effectiveness. A significant contribution of this study is the development of a framework which will guide leaders to develop HR practices in a crisis situation that are designed to drive HR effectiveness. This was developed in light of respondents’ findings and literature. This study will also help researchers to examine other variables not covered in the study, such as leadership and employee engagement that are also critical for workforce strategies in a crisis situation. This area of research can be explored further by adopting a longitudinal approach.